Regional aspects of Poland’s foreign policy (Economic and Political Thought, 2019)
Having adopted Henry Kissinger’s thesis that after 1989/1991 the worldentered a transition period from the two-polar world via the present one-polarworld /the US hegemony to the multi-polar world that followed, one mustagree with the thesis that the transition period must be characterised by farreachingdynamic of changes.Analysing Poland’s attempts to find place in the world of the transitionperiod, the author carried out an analysis of internal and external conditionsof Polish foreign policy in the period, and next included it in the analysisof selected Polish regional initiatives of the transition period. The authorconcentrates on four main initiatives of that type, i.e. the Visegrad cooperation,“the Bucharest format”, the Three Seas Initiative and the new Polishinitiative concerning the Central-European part of the Chinese project of theNew Silk Road known as the ‘16+1’ initiative.
Keywords: European Union, NATO, Visegrad Four, ‘Bucharest format’, Three Seas Initiative, Chinese New Silk Road